Prevalence Of Different Protozoan Parasites In Patients Visiting At ICDDR'B Hospital, Dhaka (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Gastrointestinal protozoan parasites are important cause of diarrhoeal illness in Bangladesh. The present study was conducted to observe the prevalence of different human gastrointestinal parasites in patients visiting a Hospital in Dhaka. Several classical techniques were employed to diagnose the causal agents which include E. histolytica, G. intestinalis, Cryptosporidium sp. and A. lumbricoides etc. A total of 540 samples from outdoor patients of ICDDRB Hospital at Dhaka was examined where different protozoan parasites including E. histolytica (1.11%), G. intestinalis (0.37%), and Cryptosporidium sp. (4.44%) were detected. Several diagnostic tools were employed that include ELISA, acid fast staining and trichrome staining techniques. Age and sex-specific susceptibility and seasonal incidence pattern were also assessed. J. Asiat. Soc. Bangladesh, Sci. 39(1): 117-123, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16040